(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status and identify factors associated with self-management behaviors among outpatients with COPD at Viet Tiep Friendship Hospital in 2025–2026. Methods: A cross-sectional descriptive study was conducted from November 2025 to March 2026 on 158 COPD outpatients, using convenience sampling. Results: The mean overall self-management score was 2.30 ± 0.36, with the highest score in daily life management (2.68 ± 0.45) and the lowest in information management (2.02 ± 0.59). Most participants had a moderate level of self-management (74.1%). Significant differences in self-management scores were found according to educational level (p = 0.0001), comorbidities (p = 0.003), and history of hospitalization due to exacerbations (p = 0.002). In addition, self-management behavior was negatively correlated with age (r = -0.23; p = 0.003) and symptom burden (r = -0.28; p = 0.009). Conclusion: Self-management behaviors among COPD patients were mainly at a moderate level and were influenced by age, educational level, comorbidities, history of exacerbations, and symptom burden. Interventions to enhance self-management should be strengthened.